Evaluation of Peak Transmission Line Conductor Reactions Under Downburst Winds Using Optimization and Simplified Approaches - Al-Issa, Atieh; El Ansary, Ayman M.; Aboshosha, Haitham; Aboutabikh, Moustafa; Ghazal, Tarek (Frontiers in Built Environment, 2019)
Transmission line structures, though designed per code provisions, suffered several failures worldwide in the past. As reported in the body of the available literature, more than 90% of those failures are due to sever localized wind events such as downbursts. Several recent studies emphasised on the importance of the conductor loads and how their forces contribute to the failure of the towers. The velocity profile and loads associated with a downburst wind field vary significantly with the change in its configuration. Previous studies, focused on identifying the critical transmission tower members that are likely to fail during a downburst event and the associated critical downburst configurations. In all these studies, a smooth terrain was assumed where the effect of terrain roughness is not considered. In the current study, an evolutionary optimization algorithm is coupled with a semi-closed form solution technique to predict the maximum conductor’s reactions under downburst wind field and the associated critical downburst configurations. A Large Eddy Simulation (LES) model of downbursts impinging on various exposure conditions, developed in a previous study, has been incorporated to predict wind forces acting on the conductor line. It is believed that the current study is the first of its kind to provide critical downburst configurations that lead to maximum conductors’ reactions while considering the effect of terrain exposure (open, countryside, suburban, and urban). Based on the optimal downburst configuration identified for each type of terrain roughness, a simple and practical approach in the form of simple equations and a set of charts to evaluate maximum reactions has been developed and validated. The simplified approach is suitable for practitioner engineers to accurately and rapidly evaluate maximum conductor reactions under downburst events considering multiple terrain conditions.